2019
DOI: 10.1111/1365-2435.13320
|View full text |Cite|
|
Sign up to set email alerts
|

More than iso/anisohydry: Hydroscapes integrate plant water use and drought tolerance traits in 10 eucalypt species from contrasting climates

Abstract: The iso/anisohydric continuum describes how plants regulate leaf water potential and is commonly used to classify species drought response strategies. However, drought response strategies comprise more than just this continuum, incorporating a suite of stomatal and hydraulic traits. Using a common garden experiment, we compared and contrasted four metrics commonly used to describe water use strategy during drought in 10 eucalyptus species comprising four major ecosystems in eastern Australia. We examined the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
64
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 54 publications
9
64
1
1
Order By: Relevance
“…In the current study, the largest increase in plant desiccation time due to leaf shedding was recorded in the arid‐zone species E. largiflorens , which started to shed leaves at higher water potentials relative to Ψ crit than other species. It is also consistent with large differences between the hydraulic vulnerability of leaves and stems recorded for this and other arid‐zone species in our sample group (Li et al ., ), suggesting that leaves may act as hydraulic fuses in delaying the onset of cavitation in more carbon‐expensive stems (Tyree & Ewers, ; Johnson et al ., ). Interestingly, the onset of leaf shedding tended to occur earlier in species from more mesic environments with lower levels of leaf and stem cavitation resistance (Li et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the largest increase in plant desiccation time due to leaf shedding was recorded in the arid‐zone species E. largiflorens , which started to shed leaves at higher water potentials relative to Ψ crit than other species. It is also consistent with large differences between the hydraulic vulnerability of leaves and stems recorded for this and other arid‐zone species in our sample group (Li et al ., ), suggesting that leaves may act as hydraulic fuses in delaying the onset of cavitation in more carbon‐expensive stems (Tyree & Ewers, ; Johnson et al ., ). Interestingly, the onset of leaf shedding tended to occur earlier in species from more mesic environments with lower levels of leaf and stem cavitation resistance (Li et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also consistent with large differences between the hydraulic vulnerability of leaves and stems recorded for this and other arid‐zone species in our sample group (Li et al ., ), suggesting that leaves may act as hydraulic fuses in delaying the onset of cavitation in more carbon‐expensive stems (Tyree & Ewers, ; Johnson et al ., ). Interestingly, the onset of leaf shedding tended to occur earlier in species from more mesic environments with lower levels of leaf and stem cavitation resistance (Li et al ., , ). This suggests a possible causal link between embolism and leaf shedding (Hochberg et al ., ), although there is still some uncertainty regarding the consistency of the shedding response with leaf water status under strongly contrasting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another knowledge gap concerns the associations between below‐ground and above‐ground hydraulic traits that determine a species' degree of iso/anisohydry. Studies have shown that where species operate along the isohydric to anisohydric continuum results from the integration of properties of different plant organs (Fu et al , 2019; Li et al , 2019; Mirfenderesgi et al , 2019). At the leaf level, more isohydric species tend to have less negative turgor loss point (Ψ TLP ), slower kinetics of stomatal opening and activation of photosynthesis, but higher intrinsic water‐use efficiency and are more likely to exhibit drought‐induced leaf shedding (Meinzer et al , 2017; Fu & Meinzer, 2019; Li et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that where species operate along the isohydric to anisohydric continuum results from the integration of properties of different plant organs (Fu et al , 2019; Li et al , 2019; Mirfenderesgi et al , 2019). At the leaf level, more isohydric species tend to have less negative turgor loss point (Ψ TLP ), slower kinetics of stomatal opening and activation of photosynthesis, but higher intrinsic water‐use efficiency and are more likely to exhibit drought‐induced leaf shedding (Meinzer et al , 2017; Fu & Meinzer, 2019; Li et al , 2019). At the stem level, more isohydric species tend to have higher hydraulic capacitance, conductivity and safety margins, but lower wood density and xylem resistance to embolism (Klein, 2014; Martínez‐Vilalta et al , 2014; Fu et al , 2019; Mirfenderesgi et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Li, X, Blackman, C. J., Peters, J. M. R., Choat, B., Rymer, P. D., Medlyn, B. E., Tissue, D. T. (2019). More than iso/anisohydry: Hydroscapes integrate plant water use and drought tolerance traits in 10 eucalypt species from contrasting climates.…”
mentioning
confidence: 99%